LIGHT-REGULATED PHOTOSYNTHETIC GENE EXPRESSION AND PHOSPHORIBULOKINASE ENZYME ACTIVITY IN THE HETEROKONT ALGA VAUCHERIA LITOREA (XANTHOPHYCEAE) AND ITS SYMBIOTIC MOLLUSKAN PARTNER ELYSIA CHLOROTICA (GASTROPODA)(1) - Soule, Kara M (Journal of phycology, 2012)
© 2012 Phycological Society of America.